CREATIVE MANAGEMENT AND INNOVATION IN EUROPE AUTOMOTIVE DIMENSION - Janáková, Hana; Zatrochová, Monika (European Scientific Journal, ESJ, 2015)
Nowadays, entrepreneurship is determined by creativity and innovations. Creativity means constantly aspiring process of innovation and progress, and both are important keys to any effort how to be success in business world. Innovation has an impact on every area of organization: design and technology, product development and value creation, creativity and problem solving, structure reorganisation etc.. Creativity and innovation in company or in entrepreneurship should be able to provide and contribute solving problems. The paper is trying to describe a creative process in management of innovation in European automotive companies in developing new products or creating new strategy. It develops the idea of how creative techniques and innovations can be used to enhance a potential of the activities of the organizational processes that can be oriented towards to achieve the objectives and specific tasks to manage.